Metode Sorogan Kitab Berbahasa Arab Di Pondok Pesantren Hasanuddin Bandar Lampung - Agus Ghafur; Doni Sastrawan; Nurkholis (Program Studi Pendidikan Bahasa Arab, 2023)
Islamic Boarding School Hasanuddin Bandar Lampung is one of the Islamic educational institutions that has the aims of realizing the values ​​of morality, skill, knowledge in order to create a truly Islamic society. This research was conducted to determine how the application of the Arabic book sorogan method at Islamic Boarding School Hasanuddin Bandar Lampung. The sorogan method is one of the traditional methods applied at Islamic Boarding School Hasanuddin Bandar Lampung to assist students in reading and understanding the yellow book which is considered still effective and relevant to be applied at Islamic Boarding School Hasanuddin Bandar Lampung. In this study the authors used a qualitative descriptive approach. The objectives of this study were (1) To describe the learning process of the yellow book with the sorogan method of the Arabic book in Islamic Boarding School Hasanuddin Bandar Lampung; (2) To describe the supporting factors for carrying out the sorogan method; (3) To describe the inhibiting factors in carrying out the Sorogan method and; (4) To describe the solution to the inhibiting factors for the ability to read the yellow book in the Arabic book sorogan method at Islamic Boarding School Hasanuddin Bandar Lampung. The data collection techniques used are through observation, documentation, and interviews. The results of this study illustrate that the Islamic Boarding School Hasanuddin has produced a number of students who are able to read the book with the initial stage of knowing the sacred, the second stage knowing Arabic grammar. And the third stage can give the real ma'na contained in the book read. Islamic Boarding School Hasanuddin Bandar Lampung did not rule out the possibility of the learning process using the sorogan method and involving senior students to directly share their knowledge.